2001
DOI: 10.1159/000047663
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Color-Doppler in the Quantification of Proximal Vertebral Artery Stenoses

Abstract: Background: Vertebrobasilar (VB) strokes appear to have the same causes as carotid strokes. Obstructive lesions of proximal vertebral arteries probably occur in about 30% of stroke patients. Purpose: Our aim was to assess the validity of color Doppler sonography compared to selective intra-arterial angiography in the quantification of proximal vertebral artery stenoses. Materials and Methods: A prospective blind study of 316 vertebral arteries was undertaken between 1996 and 1998. One hundred and fifty-eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…This resulted in lower sensitivity of DUS compared with earlier studies (de Bray et al, 2001;Hua et al, 2009). In addition, we found that our proportion of adequate visualization of the V1 segment was rather low.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This resulted in lower sensitivity of DUS compared with earlier studies (de Bray et al, 2001;Hua et al, 2009). In addition, we found that our proportion of adequate visualization of the V1 segment was rather low.…”
Section: Discussionmentioning
confidence: 76%
“…For vertebrobasilar stenosis, however, its diagnostic value is less clear (Ackerstaff, Grosveld, Eikelboom, & Ludwig, 1988;de Bray et al, 2001;Hua et al, 2009;Khan et al, 2007Khan et al, , 2009. We investigated the feasibility of DUS as a screening tool for the detection of extracranial vertebral artery stenosis in patients with posterior circulation TIA or stroke and assessed its diagnostic characteristics in comparison with CTA.…”
Section: Dus Is a Cheap And Noninvasive Imaging Technique That Has Prmentioning
confidence: 99%
“…Ostial stenosis can also be inferred from the duplex waveform of the VA. A tardus waveform or flow velocities in excess of 100 cm/s [102] are suggestive of a stenosis. A prospective blind study of 158 patients found colour Doppler to have a sensitivity and specificity of 71 and 99%, respectively, for the detection of VA stenoses of more than 70% [103].…”
Section: Atherosclerosismentioning
confidence: 99%
“…For diagnosis of stenosis > 50 % (cut-off according to TOAST [1]) we used sonography in most cases. For the extracranial internal carotid artery [5], the large intracranial cerebral arteries and the vertebrobasilar arteries [6], published criteria of stenosis were applied. 2.…”
Section: ■ Patient Selection and Clinical Assessmentmentioning
confidence: 99%